Comparing the Roles of EUS, ERCP and MRCP in Idiopathic Acute Recurrent Pancreatitis - Mohammad Taghi Safari; Mohammad Bager Miri; Shahram Ebadi; Shabnam Shahrokh; Amir Houshang Mohammad Alizadeh (Clinical Medicine Insights: Gastroenterology, 2016)
Acute recurrent pancreatitis (ARP) is defined as more than two attacks of acute pancreatitis with complete or almost complete resolution of symptoms and signs of pancreatitis between episodes. The initial evaluation fails to detect the cause of ARP in 10%-30% of patients, whose condition is classified as idiopathic ARP. Endoscopic ultrasound (EUS) has gained increasing attention as a useful imaging modality for the pancreas and the extrahepatic biliary tree. The close proximity of the pancreas to the digestive tract allows EUS to obtain detailed images of this organ. This review aims to record pancreaticobiliary endoscopic ultrasound (EUS) and other imaging modalities in the clinical management of patients with idiopathic ARP.